The GALAXIES inelastic hard X‐ray scattering end‐station at Synchrotron SOLEIL. (10th December 2018) - Ablett, J. M.; Prieur, D.; Céolin, D.; Lassalle-Kaiser, B.; Lebert, B.; Sauvage, M.; Moreno, Th.; Bac, S.; Balédent, V.; Ovono, A.; Morand, M.; Gélebart, F.; et al.
Abstract : The GALAXIES beamline, an in‐vacuum undulator hard X‐ray micro‐focused beamline at Synchrotron SOLEIL dedicated to the study of the electronic structure of materials with high energy resolution using both photoelectron spectroscopy and inelastic X‐ray scattering and under both non‐resonant and resonant conditions, is described Abstract : GALAXIES is an in‐vacuum undulator hard X‐ray micro‐focused beamline dedicated to the study of the electronic structure of materials with high energy resolution using both photoelectron spectroscopy and inelastic X‐ray scattering and under both non‐resonant (NR‐IXS) and resonant (RIXS) conditions. Due to the penetrating power of hard X‐rays and the `photon‐in/photon‐out' technique, the sample environment is not a limitation. Materials under extreme conditions, for example in diamond anvil cells or catalysis chambers, thus constitute a major research direction. Here, the design and performance of the inelastic X‐ray scattering end‐station that operates in the energy range from ∼4 keV up to 12 keV is reported, and its capabilities are highlighted using a selection of data taken from recently performed experiments. The ability to scan `on the fly' the incident and scattered/emitted X‐ray energies, and the sample position enables fast data collection and high experimental throughput. A diamond X‐ray transmission phase retarder, which can be used to generate circularly polarized light, will also be discussed in the light of the recent RIXS–MCD approach.